Features of infant exposure to tobacco smoke in a cohort study in Tasmania. Issue 1 (February 1996) - Ponsonby, A L; Couper, D; Dwyer, T
Abstract : STUDY OBJECTIVES: To document changes in smoking style around infants over time and to identify factors associated with the smoking hygiene of mothers and others. DESIGN: A population based cohort study. SETTING: Population based, involving 22% of live births in Tasmania, Australia. PARTICIPANTS: From 1 May 1988 to 30 April, 1993, 6109 infants and their mothers (89% of eligible infants) participated in the hospital and home interview of the cohort study. Infants eligible for cohort entry were those assessed at birth to be at a higher risk of SIDS. MAIN RESULTS: The overall proportion of mothers who smoked during pregnancy and postnatally did not decline. Increasing trends were found for mothers and others not smoking in the same room as baby or while holding or feeding the baby, significant over the five year period. Good smoking hygiene (mother not smoking in the same room as baby) was positively associated with–first birth (OR = 1.74 (1.30, 2.33)), low birth weight (1.69 (1.27, 2.23)), being born after 1 May 1991 (1.67 (1.33, 2.11)), and private health insurance status (1.39 (1.02, 1.90)). Good smoking hygiene was negatively associated with maternal smoking during pregnancy (0.50 (0.31, 0.80)), intention to bottle feed (0.62 (0.49, 0.78)), the level of maternal postnatal smoking, increasing numbers of smokers in the household, and parents cohabiting but unmarried. A similar analysis was conducted for other household residents who smoked. CONCLUSIONS: Changes in maternal smoking prevalence have been small. The exposure of infants to tobacco smoke postnatally has decreased significantly, although a large proportion of infants are still exposed to tobacco smoke. The identification of the above parental and infant factors associated with good smoking hygiene should be useful for health education planning.